A pre-injection assessment of CO2 and H2S mineralization reactions at the Nesjavellir (Iceland) geothermal storage site. (March 2022) - Galeczka, Iwona Monika; Stefánsson, Andri; Kleine, Barbara I.; Gunnarsson-Robin, Jóhann; Snæbjörnsdóttir, Sandra Ósk; Sigfússon, Bergur; Gunnarsdóttir, Sveinborg Hlíf; Weisenberger, Tobias B.; Oelkers, Eric H.
Abstract: The injection of water dissolved CO2 and H2 S into basalts into the Nesjavellir geothermal system (Iceland) is to begin in 2022. This study is a pre-injection investigation assessing the likely response of the fluid-rock system to the gas charged water injection. The target aquifer has a temperature of < 200 °C at the injection well, but the temperature increases to ∼300 °C towards the center of the geothermal field where the production wells are located. The aquifer has current in-situ pH values of 6.7–7.7 and CO2 and H2 S concentrations of 30.1–1079 and 60.4–505 ppm, respectively. These pre-injection aquifer fluids are saturated with respect to numerous sulfide minerals but undersaturated with respect to the major carbonate minerals. The fluid during the anticipated pilot carbon and sulfur charged water injection is expected to have a temperature of ∼84 °C, a pH of ∼4.9 and dissolved CO2 and H2 S concentrations of 1223 and 480 ppm, respectively. Geochemical modelling confirms that the injection of CO2 and H2 S charged fluids will dissolve the altered basaltic host rock near the injection well followed by the precipitation of secondary minerals including sulfides and carbonates further from the well. Calculations suggest about 70% and 100%, respectively, of this injected CO2 and H2 S will be mineralized between the injection and production wells. The increasing of the CO2 and H2 S content of the injection fluid will increase mineralization efficiency if the increased acidity of this fluid increases the mass of basalt dissolution in the subsurface. Carbon, sulfur and helium isotope systematics and abundances imply that large part of CO2 and H2 S emitted from the Nesjavellir powerplant, as well as those released from the geothermal fluids naturally originate from magmatic sources. Mass balance considerations suggest that the currently planned dissolved gas injection into the Nesjavellir system will negligibly affect the CO2 and H2 S budget of the aquifer. However, efforts to maximize the mineralization efficiency when upscaling this carbon storage system should be made to limit possible increase in reservoir fluid CO2 concentration.